Comparative carcinogenicity of ionizing radiation and chemicals : recommendations of the National Council on Radiation Protection and Measurements. (NCRP report, 1989)
This report was prepared to evaluate the extent to which the principles and methods that have been developed for use in assessing the carcinogenic risks of ionizing radiation are applicable in assessing the carcinogenic risks of chemicals. The report reviews the status of knowledge concerning the carcinogenic effects of radiation and chemicals, with particular reference to their comparative mechanisms of actions and the dose effect relationships involved. Mathematical models for predicting carcinogenic risks from radiation and chemicals are reviewed for those exposure conditions where human data are fragmentary or lacking. Major sections of the report treat the nature and mechanisms of carcinogenic effects, nature, distribution and sources of ionizing radiation in the environment; nature, distribution and sources of carcinogenic chemicals in the environment; carcinogenic effects of radiation and chemicals in humans; extrapolation from laboratory models to the human; and risk assessment. --